Design of Novel Drug as Potential Anti-Prostate Cancer Activity: Thiophene Derivatives against Prostate Cancer Cell Line as Therapeutic Agents using Pharmacokinetics Molecular Docking and DFT Studies - Atif, Hafiz Muhammad; Shahzad, Asim; Khan, Muhammad Zahid; Abbas, Muhammad Amir; Mahar, Jamaluddin (Indus Journal of Bioscience Research, 2025)
Prostate cancer (PCa) is the second most prevalent cancer in men worldwide. In the clinical practice, maintenance therapy for PCa involves the drugs that acts as antagonists or partial agonists of hormone receptors in prostate tissue. These include Cyproterone acetate, Flutamide, Bicalutamide among others. In addition to affecting the body and causing acute and long-term toxicity, these drugs may also cause drug resistance in patients. Based on the available information, our new focus has been phytochemicals that do not display any cytotoxic effects, but also possess strong androgen receptor (AR) inhibition activity. In the present study, we analyzed the geometry of thiophene derivatives and performed functionalized density functional theory (DFT) calculations of MEP and FMOs. This analysis aimed to thoroughly investigate the variations in electrostatic potential, as well the global and local reactive energy descriptors in different salvation phases. Furthermore, electrostatic potential (ESP) calculations were conducted provide a qualitative understanding of the relative polarity of molecule. The thiophene derivatives may serve as promising phytochemicals crucial for evaluating their potential in fight against prostate cancer. Since the Protein-Ligand interactions are crucial in structure-based drug design, docking results showed that thiophene derivatives revealed better binding affinity of -9.6 kcal/mol with AR compared to Abiraterone. Therefore, the obtained results suggest that all these eight phytochemicals warrant further studies for PCa prevention or treatment and show promise as active agents in pharmaceutical development.